1986
DOI: 10.1152/ajprenal.1986.250.3.f483
|View full text |Cite
|
Sign up to set email alerts
|

K+ transport by rat colon: adaptation to a low potassium diet

Abstract: Recent studies with the isolated perfused rat kidney have demonstrated the existence of an intrinsic renal adaptation to conserve K+ in response to ingestion of a low K+ diet for 3 days. To determine whether the colon alters its K+ transport properties in a similar fashion, we measured transmural 86Rb fluxes across sheets of distal colonic epithelium under short-circuit conditions. Preliminary studies using a double-isotope technique demonstrated that 86Rb and 42K fluxes were similar; therefore 86Rb flux was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…(iii) JKt after inhibition of the negative ISc was not significantly different in control and aldosterone-treated tissues, suggesting that the active absorptive capacity for K was unchanged by aldosterone addition. Previous studies of K transport from chronically treated animals also indicated that active K absorption was not altered by elevated plasma aldosterone (15,16). These three results support the model for K transport shown in Fig.…”
Section: Resultssupporting
confidence: 87%
“…(iii) JKt after inhibition of the negative ISc was not significantly different in control and aldosterone-treated tissues, suggesting that the active absorptive capacity for K was unchanged by aldosterone addition. Previous studies of K transport from chronically treated animals also indicated that active K absorption was not altered by elevated plasma aldosterone (15,16). These three results support the model for K transport shown in Fig.…”
Section: Resultssupporting
confidence: 87%
“…Taking into account that the mucosal surface is not flat, as assumed, that the real Rb uptake time is somewhat less than the Rb exposure time used, and that some of the Rb taken up has already left the cells, the total Rb uptake rate of surface and neck cells of 2.2 µmol·h -1 ·cm -2 is an underestimate and seems to be in the same order of magnitude as the parallel measured ouabain-sensitive Rb fluxes from the mucosal to the serosal side of about 1.5 and 2.5 µmol·h -1 ·cm -2 . Since Rb and K flux measurements yield similar values ( [35], Rechkemmer, unpublished data) it might be concluded that surface and neck cells are mainly responsible for K absorption.…”
Section: Cellular Rb Uptakementioning
confidence: 82%
“…Therefore, paracellular leakage could contribute to the higher colonic K + absorption during infancy. In this study we used the 86 Rb uptake assay, a well‐accepted method to determine the activity of K + transcellular transporters ( Tannen et al . 1986 , Diener et al .…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of the distal colon and measurements of K + transport using 86 Rb as a marker of K + uptake ( Tannen et al . 1986 , Diener et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation